Hotel Post Covid-19: How Preparedness Affects Guest Satisfaction In A Mid-Scales Hotel - Ersy Ervina; Riza Taufiq; Ratu Ratna (Jurnal Manajemen Indonesia, 2023)
Post-pandemic health strategies will be critical to hotel success. Guests' expectations regarding sanitation, cleanliness, safety, and health continue to rise. As a mitigation plan, hotel preparedness is essential to ensure guest satisfaction. Still, few studies examine the relationship between preparedness and guest satisfaction during the COVID-19 pandemic. This study aims to determine the effect of preparedness on guest satisfaction and assess the preparedness’s importance and performance on guest satisfaction in Bandung. The mid-scale hotel category was chosen as the unit of study since it contains the majority of hotels in Bandung. This quantitative cross-sectional study was undertaken. The data was gathered using a questionnaire survey of respondents who had stayed in the mid-scale hotel in Bandung during the pandemic. The data was analyzed using Structural Equation Modeling (SEM) PLS and Importance-Performance Map Analysis (IPMA). According to the research findings, hotel preparedness has a synergic effect on guest satisfaction. Preparedness is a process, not a product, and each practice cannot be attained separately but must be integrated to ensure guest satisfaction. This research contributes that implementing crisis management through preparedness has an essential role in guest satisfaction; practically, hotels are expected to focus on cleanliness quality and strengthen human resources by enhancing employee competencies since they have the highest level of importance in reducing the risk of COVID-19. Keywords— COVID-19, Guest Satisfaction, Mid-Scale Hotel, Preparedness